(untitled) (Baghdad Science Journal, 2019)
The present research was performed to study the qualitative and quantitative composition of epiphytic algae on the aquatic host plant Ceratophyllum demersum L. Four sites in Tigris River, at Wassit Governorate were covered, during the seasons of Autumn 2017, winter 2018, Spring 2018, and Summer 2018. The study also included measuring the physiochemical parameters (temperature of air and water, pH , water level, EC, salinity, TDS, TSS, dissolved oxygen, BOD5, alkalinity, total hardness, calcium, magnesium, total nitrogen, total phosphourus). The total number of species of epiphytic algae was145 species, 98 species belonging to Bacillariophyceae, followed by 27species of class Cyanophyceae, 19 species of class Chlorophyceae, 4 species of class Euglenophyceae, and only 1 species for each of Chrycophyceae and Rhodophceae. The total number of epiphytic algae ranged from 1681× cell/gm in Winter to 2014.95× cell/gm in Spring. The range of biodiversity indices was (1-8.2) for Richness index, (1.5-3.2) for Shannon index and (0.3-0.65) for Evenness index.